Breast Cancer Knowledge and Practice of Breast Self-Examination among Female University Students, Gaza - Samira S. Abo Al-Shiekh; Mohamed Awadelkarim Ibrahim; Yasser S. Alajerami (The Scientific World Journal)
Breast cancer is the highest public detected cancer among female population in the majority of countries worldwide. Breast self-examination (BSE) is a useful screening tool to empower women and raise awareness about their breast tissues and help detect any breast abnormalities when they occur. This study aimed to assess the level of female university students’ knowledge and practice of BSE. A self-administered questionnaire was used to assess the knowledge about breast cancer and related items, and an observation checklist was used to test practicing BSE using a breast simulator. Eighty-six students participated in the study, 58.1% studying nursing and 41.9% studying clinical nutrition in the third (40.7%) or the fourth level (59.3%). Of them, 24.4% had previous family history of breast cancer. The majority of the students (80.2%) had previous information about breast cancer acquired from different sources, university studies (57%), the Internet (45%), and social media (41%). Findings showed good scores (≥70%) regarding signs and symptoms and risk factors of breast cancer; however, low knowledge scores (<70%) were detected regarding general knowledge about breast cancer disease, methods of early detection and management, and applying steps of practicing BSE. Roughly all the students (96.5%) have heard about BSE, and 69.8% knew the time to do BSE; however, only 31.4% practice it regularly. Three barriers to practice were dominant among students who do not have a breast problem (39.7%), do not know how to do it (37.9%), and being busy 31%. On the other hand, breast cancer early detection purpose and the presence of family history of breast cancer were considered facilitators to regular practice BSE. A statistically significant relationship existed between knowledge about the steps of applying the BSE and regular practicing. A training program should be implemented to increase the level of awareness about BC and practicing BSE.